A Simplified and Efficient Protocol for Derivation and Maintenance of High‐Quality Mouse Primed Pluripotent Stem Cells Using Wnt Inhibition. (13th July 2018) - Kondo, Masayo; Sugimoto, Michihiko; Abe, Kuniya
Abstract: Epiblast stem cells (EpiSCs) are primed pluripotent stem cells (PSCs) derived from mouse postimplantation embryos. Interestingly, EpiSCs share many characteristics with human PSCs such as human embryonic stem cells (hESCs) and human induced PSCs (hiPSC). Thus, EpiSCs can serve as a model for studying primed states of pluripotency. This article describes a simple yet highly efficient protocol for EpiSC derivation and maintenance of homogenous EpiSCs using an inhibitor of WNT secretion. Using this method, EpiSCs can be readily derived from mouse strains with different genetic background including C57BL/6N. The EpiSCs derived by this protocol maintain a homogenous, undifferentiated status, yet retain high differentiation potential. Unlike EpiSCs established by the original protocol, the new EpiSC lines require the continued presence of WNT inhibitor, suggesting intrinsic differences from EpiSCs made by the original method. This new version of EpiSCs will provide clues to understand the nature of primed states of mammalian pluripotent cells and may facilitate establishment of a better protocol for directed differentiation from the primed state. © 2018 by John Wiley & Sons, Inc.